RANCANG BANGUN TURBIN KINETIK SUDU BERENGSEL LUAR SEBAGAI PEMBANGKIT LISTRIK SKALA PIKOHIDRO - Silvy Dollorossa Boedi; Alfred Noufie Mekel; Adrian Maidangkay (Otopro, 2022)
The problem of energy shortages is still a global problem which is especially felt in developing countries whose residents live in villages, which still require the development of more efficient energy sources. The problem of meeting the availability of electricity in rural areas by utilizing water energy as new and renewable energy is a long-term goal in this research.  The goal is to obtain the value of the turbine power from the turbine design which is designed to later be able to fulfill a picohydro scale power plant. The current research on kinetic turbines is a combination of two types of waterwheels, which have a vertical axis (overshot turbine and pusher turbine). Most water turbines have fixed blades. In this research, the target of the novelty is a kinetic turbine with a vertical shaft which has a hinged blade. Hinged blades are blades that can move when the flow of water hits the blades, so that on one side of the turbine it will reduce negative torque and on the other hand it will increase turbine rotation. The results of the research that became the target were to obtain a turbine design that has more optimal turbine power and efficiency, compared to a turbine that has a fixed blade, so that this externally hinged blade kinetic turbine can contribute to the provision of rural electrical energy. The optimum value in this study is the number of blades 10 and turbine power 59.01 Watt.